Os gostos de Superbonita e Contemporâneo do GNT na formação de identidades do feminino e do masculino brasileiro - Rodrigues, Carlos Augusto Alfeld (2008)
This dissertation presents a cutting of the audiovisual medias, in the case the television, considered an expressive media of the contemporary culture. It is a study of the focus given to the feminine and the masculine by two programs, Superbonita and Contemporâneo, transmitted by the cable television channel GNT, that makes part of the net of channels Globosat. Those programs are thematic, one approaches the feminine universe and the other the masculine. The main proposal of this study is centered in the investigation of like GNT it builds the discursive taste of the feminine and masculine audience. The central objective is to show how the subject's identity is constituted for the other in taste terms. With base in the identification of the figurative lines, the accomplished investigation looked for answers for as the simulacrum of the feminine and of the masculine they are enrolled in the discursive structures of Superbonita and Contemporâneo. The generated effect of sense of the cutting that those programs do of the global pattern are of the order of the spectacular, that it is originating from the staging s of the media resulting in the way for which the situations are presented in the pictures of the programs. The one that is presented is a situation no rehearsed that it stages, in action, the effects of sense of the lived experience. In the analysis of Superbonita and of Contemporâneo we used the theoretical-methodological outline of the Semiotics developed around Algirdas Julien Greimas and the Sociossemiotic by Eric Landowski prioritizing the interaction regimes as sense regimes. We treated of the subjects related to the discursive interaction, to the taste forms and the direction for the consumption that they are put in Superbonita and in Contemporâneo. Doing complex of the media it acts on three interaction regimes, where the logic that prevails is the one of the regularity and of the intentionality, the contagion happens for an impression form, in which the enunciatee will resist the incentives, to the pulses given by the enunciator. Doing to feel is explored to move in the volition of the programming, because the road traveled to encourage the volition passes for the sensibility